VITRIFICATION OF THE NUCLEAR 'SIMULATED' CESIUM WASTE BY USING BASALT GLASS - Sezen, Gul Akdag; Subasi, Metin (YILDIZ TECHNICAL UNIV, 2011)
In this study, a stable waste was simulated with a composite glass made of Cs- klinoptilolit and granulated volcanic basalt. The mixtures (samples) were prepared at the ratios of %70, %75 and %80 and kept at 1250 degrees C for 2 hours to obtain basalt glasses. Chemical contents of the Cs- klinoptilolit, the basalt glass and the simulated waste samples were determined by an ICP-MS device. Chemical strengths of the samples were also specified by ICP-MS depositing them in distilled water at 25 +/- 2 degrees C for seven days. The crystalline phases and the changes in the micro structure occurred during heating processes were studied by using a Scanning Electron Microscope (SEM-EDS) and an X-ray diffraction (XRD). The leach test of %70 and % 75 wastes uploaded glass gave values consistent with the values given in the literature within the given uncertainties. In addition, durability of the composite was decreased when the waste content was increased in the structure.
Keywords: Basalt; radioactive waste; composite material; sintering; glass; cliniptilolite; Engineering